2021
DOI: 10.4314/njtd.v17i4.5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Pentanol and Biodiesel Blends on the Performance and Emission Characteristic of Compression Ignition Engine

Abstract: Emissions from use of fossil fuels have consistently posed significant threat to the environment and wellbeing of man. This has prompted several studies aimed at finding solution to the emissions and their effects. The aim of this research is to investigate the effect of adding pentanol and biodiesel from Moringa Oleifera seed to pure diesel content of 70% by volume. pentanol and biodiesel make up the remaining 30 percent by volume and were also varied, with pentanol percentage being increased from 2 percent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…a similar engine pollution reduction result was reported by (Kaisan et al 2017). (Ibrahim et al, 2020) investigated the effect of combining pentanol in modest percentages with moringa oleifera biodiesel and found that while fuel quality and engine brake power improved, NOx emissions increased. (Elfasakhany 2015) found that blending isobutanol with gasoline lowered engine cylinder pressure, brake power, and exhaust gas temperature compared to pure gasoline.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…a similar engine pollution reduction result was reported by (Kaisan et al 2017). (Ibrahim et al, 2020) investigated the effect of combining pentanol in modest percentages with moringa oleifera biodiesel and found that while fuel quality and engine brake power improved, NOx emissions increased. (Elfasakhany 2015) found that blending isobutanol with gasoline lowered engine cylinder pressure, brake power, and exhaust gas temperature compared to pure gasoline.…”
Section: Introductionsupporting
confidence: 66%
“…As poor fuel quality may be measured by engine emission, where these emissions pose a threat to the environment we're living in, different sources of energy are being explored to have a more economical, sustainable manner (Ibrahim et al 2020). For a peaceful solution, improving the quality of these fossil fuels is considered.…”
Section: Introductionmentioning
confidence: 99%
“…These advancements in biofuel technology bear particular relevance to regions such as Iraq, where diesel engines power a substantial proportion of vehicles, machinery, and electricity generators [26,27]. The resultant pollutant emissions from these engines contribute significantly to air quality degradation, yielding profound implications for environmental and public health.…”
Section: Introductionmentioning
confidence: 99%